(Step)Parenting Attitudes and Expectations: Implications for Stepfamily Functioning and Clinical Intervention. Issue 3 (July 2014) - Jensen, Todd M.; Shafer, Kevin; Larson, Jeffry H.
Stepfamilies face many challenges. Research and clinical work with stepfamilies have tended to use the family systems or developmental perspectives, while overlooking how cognitive processes may influence stepfamily functioning. We fill this gap in the literature by analyzing a sample from the Relationship Evaluation (RELATE) questionnaire database to examine the influence of (step)parenting cognitions on stepparenting issues and relationship satisfaction. Results indicate that individuals who report placing top priority on their own biological children expect their stepchildren to be obedient to them, and those who believe that the children interfere with the new parental relationship report higher levels of stepparenting issues and lower levels of relationship satisfaction. Clinical implications and limitations are discussed.